A System dynamics analysis of the factors influencing the promotion of prefabricated decoration, based on a co-occurrence network - Yingchen Wang; Jingtian Liu; Guiwei Zhang; Xiaoxiao Geng; Yan Liu (PLoS ONE, 2025)
Prefabricated decoration effectively addresses resource waste, environmental pollution, and quality issues associated with traditional decoration methods. It also enhances the functionality of prefabricated buildings and offers promising market potential. Currently, insufficient attention from both the public and managers hinders prefabricated decoration development. To address this, this study analyzed 68 relevant documents from the China National Knowledge Infrastructure and Web of Science databases, identified 34 factors affecting the promotion of prefabricated decoration, and constructed a co-occurrence network model based on an adjacency matrix. The centrality index was used to identify four key factors related to the three core stakeholders: government support, technical level, developers’ willingness to use, and consumers’ willingness to use. Subsequently, the four key factors were simulated using Vensim software. The evolutionary trends of the system and the interactions between these factors were analyzed. The findings reveal that both developers and consumers show strong sensitivity to financial subsidies. As a result, the government can effectively increase subsidies to encourage adoption of prefabricated decoration. Additionally, enhancing the use of BIM technology throughout the project life cycle has been shown to promote synergy within the industrial chain, thereby improving promotion efficiency. Consumer feedback is essential for ensuring policy accuracy and plays a crucial role in advancing the industry's development. The novel contributions of this paper include the integration of co-occurrence network analysis with a system dynamics model, identifying key factors through the co-occurrence network, and uncovering the complex interactions between these factors via the system dynamics model. Based on the simulation results, this study predicts the development prospects of prefabricated decoration, offering both a theoretical foundation and practical guidance for policy formulation and promotion strategies.